2014
DOI: 10.1080/00103624.2014.904334
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Affect Yield, Essential Oil Compound, and Rhizosphere Microflora of Vetiver (Vetiveria zizanioidesLinn. nash) Grass

Abstract: The effects of heavy metals [chromoium (Cr), cadmium (Cd), lead (Pb) and nickel (Ni)] on the yield, khusimol content in the essential oil, accumulation of metals, and rhizosphere microflora of vetiver (Vetiveria zizanoides) were studied in a pot experiment. The shoot yield and khusimol content in oil of vetiver were enhanced by the application of moderate amount of metals to soils. The application of Cr, Pb, and Ni had deleterious effects on the root and essential oil yield. The application of high levels of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
2
13
2
Order By: Relevance
“…In this study, the soil pollution by TE did not significantly alter EO composition. This result is not in agreement with some previous studies, which showed that the presence of TE in soil, among other environmental conditions, was susceptible to affecting EO composition and quality [ 22 , 24 ]. Notably, it was suggested that the stress induced by the presence of TE resulted in a modification of the secondary metabolism [ 24 , 49 , 50 , 51 ].…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In this study, the soil pollution by TE did not significantly alter EO composition. This result is not in agreement with some previous studies, which showed that the presence of TE in soil, among other environmental conditions, was susceptible to affecting EO composition and quality [ 22 , 24 ]. Notably, it was suggested that the stress induced by the presence of TE resulted in a modification of the secondary metabolism [ 24 , 49 , 50 , 51 ].…”
Section: Discussioncontrasting
confidence: 99%
“…This result is not in agreement with some previous studies, which showed that the presence of TE in soil, among other environmental conditions, was susceptible to affecting EO composition and quality [ 22 , 24 ]. Notably, it was suggested that the stress induced by the presence of TE resulted in a modification of the secondary metabolism [ 24 , 49 , 50 , 51 ]. This could either lead to an inactivation of enzymes involved in the EO biosynthesis pathways, in the case of Mentha arvensis L., Mentha piperita L. and Vetiveria zizanioides Linn.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Recent studies by Chen et al (2012), Prasad et al (2014) and Singh et al (2015) have solely focused on the phytoassessment of a single metal accumulation. However, there Abstract Three different types of low cost soil amendments, namely, EDTA, elemental S and N-fertilizer, were investigated with Vetiver grass, Vetiveria zizanioides (Linn.)…”
mentioning
confidence: 99%
“…Vetiver is tolerant to Pb (Danh et al, 2012;Pidatala et al, 2016;Bahraminia et al, 2016), Cu and Zn (Hego et al, 2009;Vargas et al, 2016), B (Angin et al, 2008), Cr (Shahandeh and Hossner, 2000;Danh et al, 2012), Al (Truong, 1999;Danh et al, 2009), Ni (Prasad et al, 2014), Fe (Banerjee et al, 2016(Banerjee et al, , 2019, As (Datta et al, 2011), Cd (Ondo Zue Abaga et al, 2014, and Hg (Danh et al, 2009;Lomonte et al, 2014). TE are usually accumulated in vetiver roots (Phusantisampan et al, 2016), although some ecotypes show higher concentrations in shoots (e.g., Zn in the Ratchaburi ecotype) (Roongtanakiat and Sanoh, 2011), depending on site conditions and time.…”
Section: Perennial Grass Cropsmentioning
confidence: 99%